2019
DOI: 10.1039/c8ta10686j
|View full text |Cite
|
Sign up to set email alerts
|

One-step construction of core/shell nanoarrays with a holey shell and exposed interfaces for overall water splitting

Abstract: The Ni3S2/VO2 core/shell nanoarray exhibits outstanding catalytic activities rendered by the synergistic effects of 1D morphology, enriched holes, exposed interfaces and conductive substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…water splitting, which only took a low potential of 1.42 V to attain a current density of 10 mA cm -2 47. The astonishing catalytic activity originated from the interfaces which gave rise to a low-energy-level d band center and a low Gibbs free energy.…”
mentioning
confidence: 99%
“…water splitting, which only took a low potential of 1.42 V to attain a current density of 10 mA cm -2 47. The astonishing catalytic activity originated from the interfaces which gave rise to a low-energy-level d band center and a low Gibbs free energy.…”
mentioning
confidence: 99%
“…The material acquires a voltage of 1.42 mV for current densities of 10 mA cm −2 along with the largest ECSA value of 24.09 mF cm −1 , Tafel slope value of 47 mV dec −1 , and stability for at least 15 h in an alkaline medium. The excellent electrocatalytic performance overall is mainly credited to the synergistic effect of enriched holes, 1D morphology, exposed interfaces, and the conductive substrate [134] …”
Section: Materials For Oermentioning
confidence: 99%
“…The Ni−Fe‐OH@Ni 3 S 2 required only a low overpotential of 165 mV to deliver a current density of 10 mA cm −2 toward OER. In addition, The core/shell Ni 3 S 2 /VO 2 nanoarrays were fabricated as bifunctional electrocatalysts for both HER and OER via a one‐step hydrothermal method (Figure a), XPS results showed that a positive shift of the binder energy of the Ni 2P spectra of Ni 3 S 2 /VO 2 can be observed compared with pure Ni 3 S 2 , suggesting the strong electronic interaction between VO 2 and Ni 3 S 2 , which will lead to the redistribution of charge on their interfaces.…”
Section: Interface Engineering Of Binder‐free Electrocatalystsmentioning
confidence: 99%